An Empirical Study of Factors Influencing Digital Banking Intention Use in Indonesia - Elissa Dwi Lestari; Dini Gustianawati Sutarja; Helena Dewi (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The banking industry is one of the service industries that contributes to national income and serves as an intermediary institution to accommodate public funds and channel them back to productive economic activities. This study will look into the factors that influence customers' intentions to use digital banking and utilize it to their advantages and future advancements. This research uses TAM (technology acceptance model) as framework to explain the intention to adopt digital banking phenomenon. In addition to TAM components of perceived ease of use and perceived usefulness, this research also put perceived risk, trust, and inconvenience into the TAM framework. Design/methodology/approach: This study using quantitative descriptive research design with conclusive research. This study use non-probability sampling with judgmental technique to 140 respondents that meet the research sampling criteria. IBM SPSS version 24 is used for multiple regression data processing and analysis. Findings: The findings show that perception ease of using, perceived usefulness, and perceived risk have no effect on intention to use digit banking. Furthermore, the findings confirm the positive influence of trust and convenience on the intention of using digital banking. Research limitations/implications: The study used Google Forms, which limited respondents' time to answer, and respondents' opinions may be prejudiced. This study's sample size reduced respondents' general representation, and the results were limited to one country. Future academics may add others variables that affect digital banking adoption into the framework. The researchers also recommend bigger sample sizes with a more diverse demographic profile of respondents. Practical implications: Digital banks might emphasize trust and convenience to attract new consumers. Delivering on promises will build trust in services. Digital bank providers can also emphasize their technology's convenience, which allows clients to do financial transactions anywhere and anytime. Originality/value: This study will serve as a reference for digital bank providers in promoting the usage of digital bank services in order to accelerate Indonesian digital bank adoption, which is still lagging behind that of other Asian countries. Paper type: Research paper